Sol-gel synthesis and characterization of iron-silica aerogel and xerogel using rice husk ash as silica precursor / Khomarul Nafisyah Maamur - Maamur, Khomarul Nafisyah (2010)
Rice husk ash (RHA) has been used as an alternative precursor for silicon alkoxide in preparing porous silica using sol gel process. The use of rice husk has the benefit not only of producing valuable silica powder but also of reducing environmental problem associated with RHA disposal and the high cost of toxic silicon alkoxide precursors. This study is aimed to synthesize iron incorporated silica aerogel and xerogel from rice husk ash as silica precursor. Iron in the form of hydrated iron nitrate with compositions in the range of 3-17wt% (Fe203/Fe203+Si02) were used as iron source. The synthesis of iron doped aerogel was done by supercritical drying at temperature of about 250°C and pressure of about 5.9 MPa (850 psi) while xerogel was formed by drying the aquagel in an oven at 11 O°C for 24 hours. Characterization of samples were done using BET surface area analyze for pore and surface characteristics, X-Ray Diffractometer (XRD) for phase identification and Scanning Electron Microscope (SEM) for microstructural development. Specific surface area of the prepared silica aerogel and xerogel was 597.9 m2/g and 340.5 m2/g respectively. Specific surface area of iron incorporated silica aerogels and xerogels showed a decreasing pattern. The results obtained from SEM demonstrated that the iron particles were successfully incorporated and homogeneously dispersed throughout the silica matrix. After heat treatments, aerogel sample doped with 7.3 wt% iron at temperature 1100°C showed the presence of maghemite (y-Fe203) and while other samples showed the presence of magnetite (Fe304) and hematite (a-Fe203). Results from FTIR and TGA were found to be consistent with the XRD and SEM. Upon application on column chromatography, silica aerogel prepared from RHA had shown potential as packing material for colour separation of Purple Orchid (Cattleya bowringiana) flower. Three different colours; green, blue, and purple were successively parted from the column. Colour separation did not occur with the iron incorporated silica aerogel. Instead, the colour of the sample turned from red to blue possibly due to the chemical reaction taking place between iron and the sample.